Entrepreneurial Climate in India, China and the USA - Mahalakshmi S; Thiyagarajan S; Ranbir Sodhi; Naresh G (Organizations and Markets in Emerging Economies)
Entrepreneurship plays a vital role in the process of wealth creation and improving the standard of living of the people through large-scale employment generation. So this study aims to identify the critical factors among the entrepreneurial framework conditions (EFC) and entrepreneurial behaviour and attitudes (EBAA) in enhancing the entrepreneurship climate in the United States of America (USA), China and India. The data for the study is collected from GEM (Global Entrepreneurship Monitor) on EBAA and EFC. Exploratory factor analysis was attempted initially to reduce the EBAA and EFC data into manageable factors. Further, confirmatory factor analysis was attempted to cross-validate the results.